2017
DOI: 10.1016/j.pediatrneurol.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Large-Vessel Vasculopathy in Children With Sickle Cell Disease: A Magnetic Resonance Imaging Study of Infarct Topography and Focal Atrophy

Abstract: Background Large-vessel vasculopathy (LVV) increases stroke risk in pediatric sickle cell disease (SCD) beyond the baseline elevated stroke risk in this vulnerable population. The mechanisms underlying this added risk and its unique impact on the developing brain are not established. Methods We analyzed magnetic resonance imaging (MRI) and angiography (MRA) scans of 66 children with SCD and infarcts by infarct density heatmaps and Jacobian determinants, a metric utilized to delineate focal volume change, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 49 publications
5
45
1
Order By: Relevance
“…Deformation Index was positively correlated with hemoglobin in the frontal, parietal and temporal lobes but not in the occipital lobe. This finding aligned with reported regional WM volume loss, silent stroke distribution, and decreased white matter integrity in SCD patients . More specifically, regions susceptible to anemia were generally restricted to the bilateral deep white matter of watershed regions, and the territory of the middle cerebral artery.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Deformation Index was positively correlated with hemoglobin in the frontal, parietal and temporal lobes but not in the occipital lobe. This finding aligned with reported regional WM volume loss, silent stroke distribution, and decreased white matter integrity in SCD patients . More specifically, regions susceptible to anemia were generally restricted to the bilateral deep white matter of watershed regions, and the territory of the middle cerebral artery.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, acute anemic events has been identified as risk factors for children with, and without, SCD . Colocalized tissue atrophy, and elevated oxygen extraction, in deep‐white matter watershed regions, have been reported in children with SCD, even in the absence of white matter hyperintensities. We hypothesize that maintaining a high hemoglobin count in patients with hemoglobinopathies during school age years will help preserve white matter volumes, although a longitudinal study is necessary to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…It implies that WMHs are occurring in borderzone regions where perfusion is inherently decreased in anyone. Studies from Numaguchi, Baldeweg, Guilliams and Ford in SCD patients also support that conclusion. Our O 2 delivery T‐score maps agrees with the observations of Fields et al, who demonstrated increased O 2 extraction fraction in watershed areas .…”
Section: Discussionmentioning
confidence: 64%
“…45 We identified a region of increased OEF in the deep supraventricular white matter, corresponding to the internal borderzone, which we and others have demonstrated to be at highest risk of infarction in SCA. 46,47 We propose that in addition to flow-limiting pathologies, oxygen-limiting pathologies would further increase ischemic vulnerability of the internal borderzone (or watershed region), as signaled by high OEF. In children with SCA, CaO 2 -lowering stressors could be common SCA complications, such as worsening of anemia or hypoxemia during acute chest syndrome.…”
Section: Discussionmentioning
confidence: 99%